O problema da otimização do gás lift com alocação de poços aos separadores de produção - Chaves, Gabriela Souza (2018)
The development of optimization methodologies is very important for the production phase of an oil field, since small changes in the operational point can increase the revenue without adding costs. The objective of this work is to optimize the oil production at the arrival of the production unit considering the allocation of the wells to the production separators. The constraints are related to the water, oil and gas processing capacities. The decision variables are the gas-lift rate of the wells, the separators pressure and the allocation wells - separators. Thus, the problem is a mixed integer linear programming. The performance curves of the wells were linearized by SOS2 interpolation. These curves were generated by the own multiphase flow model simulation and using the same computational language (Pyhton) than the optimization. This same computational language enables a robust formulation to communicate the simulation and the optimization. The study concluded that the operational point, a result of optimization, is highly sensitive to platform capabilities. In addition, a quality of the manifold performance curve is most significant in more restricted production scenarios.